SENIOR SCHOOL STUDENTS’ PREFERENCE OF TEST FORMAT AND THEIR ACADEMIC PERFORMANCE IN MATHEMATICS - ADENIYI, Saidat M.; RASAQ, Taiwo; AMEEN, Saka K.; SALMAN, Medinat F. (Ilorin Journal of Education, 2023)
The poor performance of students in mathematics at both internal and external examinations have been traced to a host of factors which are related to teachers, parents and students. But does the format in which these examinations are prepared contributes to the students’ poor performance? Then, it is imperative to examine students’ preferred test format and their academic performance in mathematics. The objectives of this study are to determine students preferred test format; the likely reasons for their choice of test format; influence of gender and subject combination on their choice of test format; and compare their academic performance in mathematics based on test format preference. Three hundred (300) senior school students were randomly sampled to participate in this study. The instruments for data collection were researchers’ designed questionnaire and a performance test. The instruments were validated and reliability indices of 0.87 and 0.76 were obtained using test-retest method. Frequency, simple percentage, chi-square and t-test were used for analyzing and testing the hypotheses. The result of the study indicated that senior school students prefer multiple choice tests for mathematics examination; the reason for their preference was largely based on their belief that multiple choice tests are easy to pass; there is significant difference in the choice of test format based on gender and subject combination; and there is no significant difference in the performance of students based on their test format preference. The study recommends among others that teachers should use suitable test format for assessing the students. Also, since the competence in mathematics can be demonstrated through conceptual and procedural knowledge, mathematics teachers should continuously assess students so that they can demonstrate in-depth knowledge of problem solving rather than just selecting from alternatives